The Communication of Social Meaning in Conversation - Warnke, Lena. (Tufts University. Tisch Library., 2024)
Thesis (Ph.D.)--Tufts University, 2024.; Submitted to the Dept. of Psychology.; Advisor: Jan de Ruiter.; Committee: Gina Kuperberg, Kristen Bottema-Beutel, and Ariel Goldberg.; Keywords: Psychology, and Linguistics.